Characteristics of wildfire-igniting lightning in the western United States - Burris, Lucy Ellen, author; Sibold, Jason, advisor; Kelly, Eugene, committee member; Hoeting, Jennifer, committee member (Colorado State University. Libraries, 2015)
Annually, over half the wildfires on federal lands in the conterminous western United States are caused by lightning. However, broad-scale characteristics of wildfire-igniting lightning flashes are poorly understood, and limit our ability to predict what role climate change might have on lightning patterns and in turn on future patterns of wildfire. I investigated lightning-wildfire relationships by comparing the characteristics of lightning flashes that start fires to those that do not across 29 ecoregions in the western US from 2003-2007. After accounting for ecoregional variation, I found little meaningful difference in characteristics of igniting flashes including the proportion of positive flashes, proportion of negative flashes with long continuing current, number of strokes per flash (multiplier), or flash peak current (all attributes thought to be related to ignition potential). In contrast, I found that wildfires are associated with significantly higher lightning flash densities near fire locations compared to further away. However, the role of flash density varied significantly between ecoregions. Given the non-uniqueness of igniting flashes, simple proxies such as storm frequency or intensity may be sufficient to estimate likelihood of lightning ignitions under changing climatic conditions. However, these estimates must be mediated based on ecosystem response to potential ignitions.
Keywords: lightning density; lightning flash; long continuing current; wildland fire